2021
DOI: 10.1038/s41598-021-83856-z
|View full text |Cite
|
Sign up to set email alerts
|

Solidified glomerulosclerosis, identified using single glomerular proteomics, predicts end-stage renal disease in Chinese patients with type 2 diabetes

Abstract: Few histological prognostic indicators for end-stage renal disease (ESRD) have been validated in diabetic patients. This biopsy-based study aimed to identify nephropathological risk factors for ESRD in Chinese patients with type 2 diabetes. Histological features of 322 Chinese type 2 diabetic patients with biopsy-confirmed diabetic nephropathy (DN) were retrospectively analysed. Cox proportional hazards analysis was used to estimate the hazard ratio (HR) for ESRD. Single glomerular proteomics and immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…Univariate and multivariate analysis showed that diabetes duration and baseline HbA1c were not associated with progression to ESKD in patients with T2D (data not shown), which was consistent with previous studies ( 21 , 25 , 48 ). In a prospective analysis of patients with T2D, the coefficient of HbA1c variation, not the mean of serially measured fasting plasma glucose, was predictive of the development of renal complications and diabetes-related outcomes ( 49 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Univariate and multivariate analysis showed that diabetes duration and baseline HbA1c were not associated with progression to ESKD in patients with T2D (data not shown), which was consistent with previous studies ( 21 , 25 , 48 ). In a prospective analysis of patients with T2D, the coefficient of HbA1c variation, not the mean of serially measured fasting plasma glucose, was predictive of the development of renal complications and diabetes-related outcomes ( 49 ).…”
Section: Discussionsupporting
confidence: 91%
“…Arteriolar hyalinosis and arteriosclerosis were assessed and scored according to the RPS-DKD classification ( 24 ). In addition to the RPS-DKD classification, other pathological lesions, including global glomerulosclerosis, segmental sclerosis, extracapillary hypercellularity ( EXHC), the Kimmelstiel–Wilson (KW) lesion, mesangial proliferation, and capillary microaneurysms, were evaluated ( 25 ). The detailed definition of pathological parameters is listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study using single-nephron proteomic analysis and immunohistochemical staining suggested complement factors such as C3, C8, and C9 are overactivated in solidified glomerulosclerosis in patients with DN. Solidified glomerulosclerosis was shown to be an independent pathological finding that predicts future diabetic ESRD [ 43 ]. C9 binds C8 in the C5b-8 complex and forms the MAC that causes cellular and organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…To identify relevant studies, we searched databases, such as PubMed, Excerpta Medica Database, Cochrane library, and Web of Science, on September 2023 with medical subject heading terms and text words in multiple combinations: "diabetic nephropathy", "diabetic kidney disease", "crescent", and "extracapillary hypercellularity." Accordingly, 4 retrospective cohort studies including DKD patients were used because information on HRs of the ESKD outcome and the presence of glomerular crescents were available (22,23,24,25). The pooled effect estimates and associated 95% CIs were calculated using a common effect model.…”
Section: Discussionmentioning
confidence: 99%